Isolasi dan Identifikasi Mikroorganisme yang Berasosiasi dengan Tanaman Kantong Semar: (Nepenthes sp.) - Lilik Hevinovisa; Ardi Mustakim (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
The pitcher plant (Nepenthes sp.) is a type of predatory plant typically found in tropical regions and has a pitcher structure designed to attack insects. The pitcher's structure acts as a small ecosystem that supports a variety of microorganisms, both those living on the surface (epiphytes) and those within the tissue (endophytes). This study aimed to extract and identify microorganisms present on the surface and interior of the pitcher plant. Samples were taken from peat swamps and separated using Nutrient Agar (NA) for bacteria and Potato Dextrose Agar (PDA) for fungi. The discovery process involved examining morphological characteristics both visually and under a microscope. The results revealed differences in the types of microorganisms between the outside and inside of the pitcher, influenced by the microenvironmental conditions in each area. These findings can serve as a foundation for further study of the bioactive potential of microorganisms from the pitcher plant.